Nutrient Removal by Rice Cultivated in Newly Opened Wetland Rice in Bulungan District, East Kalimantan - Sukristiyonubowo, .; Nugroho, Kusumo; Vadari, Tagus (UNIVERSITY OF LAMPUNG, 2012)
Highly weathered Indonesian soils and potential acid sulphate soils are mainly granted for developing newlyopened wetland rice field to meet rice growing demand in Indonesia. Nutrient removal by rice harvest product ofCiliwung variety planted in newly opened wetland rice was studied in Bulungan District, in 2009. The aims were toexamine the nutrient taken out by rice harvest product and to properly manage its fertility status to sustain ricefarming. Six treatments were studied including T0: farmers practices, T1: farmer practices + compost + dolomite, T2:NPK recommended rate, N and K were split two times, T3: NPK recommended rate, N and K were split three times,T4: NPK recommended rate, N and K were split three times + compost + dolomite and T5: NPK recommended rate,N and K were split two times + compost + dolomite. The results indicated that the highest concentrations of N, P,and K in rice grain and rice straw were observed at NPK with recommendation rate in which N and K were split threetimes + straw compost + dolomite (T4). The T4 (NPK with recommendation rate in which N and K were split threetimes + straw compost + dolomite) also showed the highest nutrient removal by harvest product. Depending on thetreatments, total nutrients removal through rice grains and rice straw varied from 61.81 to 101.71 kg N, 4.31 to13.69 kg P and from 95.77 to 171.16 kg K ha-1 season-1, meaning that at least about 137 to 225 kg urea, 50 to 160kg SP-36 and 190 to 339 kg KCl ha-1 season-1 should be given to replace nutrient removed by harvest product andto avoid any nutrients depletion. When all rice straws were returned to the field as compost, about 55 to 133 kg urea,25 to 110 kg SP-36 and 10 to 19 kg KCl ha-1 season-1 should be added to substitute nutrient removed by rice grain.[How to Cite: Sukristiyonubowo, K Nugroho and T Vadari. 2012. Nutrient Removal by Rice Cultivated in Newly Opened Wetland Rice in Bulungan District, East Kalimantan. J Trop Soils 17: 115-120. Doi: 10.5400/jts.2012.17.2.115]Â [Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.2.115]